Mechanistic Roles of Matrilin-2 and Klotho in Modulating the Inflammatory Activity of Human Aortic Valve Cells - Erlinda The; Qingzhou Yao; Peijian Zhang; Yufeng Zhai; Lihua Ao; David A. Fullerton; Xianzhong Meng (Cells, 2020)
Background: Calcific aortic valve disease (CAVD) is a chronic inflammatory disease. Soluble extracellular matrix (ECM) proteins can act as damage-associated molecular patterns and may induce valvular inflammation. Matrilin-2 is an ECM protein and has been found to elevate the pro-osteogenic activity in human aortic valve interstitial cells (AVICs). Klotho, an anti-aging protein, appears to have anti-inflammatory properties. The effect of matrilin-2 and Klotho on AVIC inflammatory responses remains unclear. Methods and Results: Isolated human AVICs were exposed to matrilin-2. Soluble matrilin-2 induced the production of ICAM-1, MCP-1, and IL-6. It also induced protein kinase R (PKR) activation via Toll-like receptor (TLR) 2 and 4. Pretreatment with PKR inhibitors inhibited NF-κB activation and inflammatory mediator production induced by matrilin-2. Further, recombinant Klotho suppressed PKR and NF-κB activation and markedly reduced the production of inflammatory mediators in human AVICs exposed to matrilin-2. Conclusions: This study revealed that soluble matrilin-2 upregulates AVIC inflammatory activity via activation of the TLR-PKR-NF-κB pathway and that Klotho is potent to suppress AVIC inflammatory responses to a soluble ECM protein through inhibiting PKR. These novel findings indicate that soluble matrilin-2 may accelerate the progression of CAVD by inducing valvular inflammation and that Klotho has the potential to suppress valvular inflammation.